Investigating the Consolidation Behaviour of Cement-Bentonite Barrier Materials Containing PFA and GGBS - Muhammad A. Walenna (Civil Engineering Journal, 2023)
Cement-Bentonite (CB) barriers are expected to become a sustainable and reliable engineering solution. The deformation of CB is of interest to engineers to comprehend, particularly how CB responds to changes in loading during its construction and service life. The purpose of this study was to examine how samples of CB mixtures behaved during consolidation. This study investigated: (1) the influence of curing time and constituent materials on the consolidation properties of CB samples, (2) the volumetric change and the rate of volumetric change in response to a specific loading condition via consolidation tests. For this purpose, a laboratory consolidation test with a load range of 50 to 3200 kPa was carried out in accordance with BS 1377-7:1990 using the oedometer apparatus. This study discovered that the consolidation characteristics of CB samples are similar to those of overconsolidated soil. The CB sample became more resistant to consolidation under varying loads as curing progressed. The presence of more bentonite resulted in an increase in the recompression index. The inclusion of GGBS contributed to the consolidation characteristics of CB through the following mechanisms: (1) the significant decrease of the degree of consolidation with a curing period longer than 28 days, despite the slow strength development of the early-age curing; (2) the increase of the preconsolidation pressure; and the addition of GGBS was found to be more effective than the addition of more bentonite in increasing the preconsolidation pressure. Doi: 10.28991/CEJ-2023-09-03-02 Full Text: PDF